Life Quality of Elderly with Hypertension - Prianti, Britania; Mugianti, Sri; Mujito, Mujito (Poltekkes Kemenkes Malang, Campus III Blitar, 2025)
Hypertension is one of the main problems among the elderly because it is one of the causes of serious complications that can be fatal, one of which is a decrease in quality of life. The aim of this research is to determine the level of quality of life of hypertensive elderly based on physical, psychological, social relations and surrounding environmental aspects. The method used is descriptive quantitative with a cross sectional approach. The sample in this study was 28 people suffering from hypertension at the Tresna Werdha Blitar Social Services UPT in Tulungagung, taken using a total sampling technique. The instrument used was the WHOQOL-BREF questionnaire. The research results showed that 64.3% of respondents had a good quality of life. The quality of life of respondents in the physical aspect was 64.3% good, in the psychological aspect it was 57.1% good, in the social relations aspect it was 53.6% good, and in the environmental aspect it was 53.6% fair. It is important to implement CERDIK and PATUH as well as adopt a clean and healthy lifestyle to minimize the decline in quality of life.